Perjudian Berdasarkan Hukum Pidana Positif Indonesia dan Hukum Pidana Islam - Handoko, Duwi; Marlina, Tat (Institut Agama Islam Negeri Ponorogo, 2023)
Legal review regarding the status of state finances within the scope of state-owned enterprises and the resolution of the problems of corruption, which uses a type of normative legal research which uses a statutory approach, and legal history, as well as legal politics, that there are research results which find that first , positive laws such as the 1945 Constitution and the package of state finance laws have provided legal certainty regarding the status of state finances within the SOE Persero environment as state finance, which for the sake of creating a governance mechanism and an accountable, transparent, prudent state financial accountability in the end will create prosperity for all people. There is a consequence that all legal arrangements that are different and raise doubts must still refer to the provisions of the 1945 Constitution and the package of laws on state finances. Second, regulation regarding the legal status of finance within the BUMN Persero regarding the problem of state losses in the problem of resolving a criminal act of corruption in which the directors and commissioners of a Persero BUMN can be subject to criminal charges of corruption (besides civil and administrative) if in the management of state finances within the BUMN Persero , the decisions and actions fulfilling the elements of the offense regulated in Article 2 paragraph (1) and Article 3 of Law no. 31 of 1999 jo. UU no. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, without having to prove before hand whether there are state losses caused by these decisions and actions. This is based on good will to save state finances in order to increase the country's economic growth and the welfare of all the peopleSeseorang yang memiliki sifat buruk, seperti menjadi seorang penjudi secara psikologis lebih takut terhadap kenyataan yang akan dihadapi ketika berhadapan dengan polisi dari pada pemidanaan yang akan dijatuhkan oleh hakim apabila dalam perbuatannya tersebut dirinya tertangkap. Perjudian menurut hukum Islam tidak mendapatkan sanksi yang berat seperti pembunuhan secara sengaja maupun perbuatan zina. Meski perjudian tetap termasuk perbuatan dosa bagi para pelakunya. Tujuan penelitian ini adalah untuk membandingkan ketentuan pidana bagi pelaku perjudian ditinjau dari hukum pidana positif Indonesia dengan hukum pidana Islam. Metode penelitian ini adalah penelitian hukum normatif, yaitu melakukan kajian terhadap literatur-literatur yang terkait dengan objek penelitian. Ketentuan pidana terhadap pelaku perjudian ditinjau dari aspek hukum pidana positif adalah lebih beratnya ancaman pidana bagi pemain judi online apabila dibandingkan dengan pelaku judi konvensional. Ketentuan pidana terhadap pelaku perjudian ditinjau dari aspek hukum Islam adalah terdapat dosa yang besar dan beberapa manfaat bagi manusia, tetapi dosanya lebih besar dari manfaatnya. Pada saat ini, setiap orang berpotensi bermain judi secara online. Dengan demikian, diperlukan pendekataan khusus dari sisi keagamaan untuk mencegah perbuatan melawan hukum tersebut.